Shear strength, compressibility, and consolidation behaviour of expansive clay soil stabilized with lime and silica fume - Almuaythir, Sultan; Muhammad Syamsul Imran, Zaini; Muzamir, Hasan (Nature Publishing Group, 2025)
Expansive clay soils cause structural failures in construction due to volume changes with moisture, but hydrated lime effectively stabilizes them by improving shear strength and reducing plasticity. To address environmental concerns with traditional stabilizers like cement, silica fume, a byproduct of the silicon industry, is now being used as a supplementary additive to enhance stabilization. In this study, the combined effects of hydrated lime and silica fume addition on the shear strength and consolidation behaviour of expansive clay soils are presented. An experimental programme was performed in the laboratory using different ratios of lime and silica fume to determine changes in soil properties. Experimental results indicate that the inclusion of silica fume and lime leads to a 35% increase in shear strength and a 28% reduction in compressibility compared to untreated soil. Moreover, the peak deviatoric stress increased from 540.55 kPa in untreated soil to 624.95 kPa in soil stabilized with 9% lime and 9% silica fume. The results clearly demonstrated that the union of these two additives improves shear strength and consolidation characteristics to stabilize expansive clays which is eco-friendlier and more promising solution. The insights obtained from this research will help us to develop soil stabilization techniques for better in-situ soil performances and hence, sustainable construction.